Comparative Analysis of Formal Model Checking Tools for Security Protocol Verification - Patel, Reema; Borisaniya, Bhavesh; Patel, Avi; Patel, Dhiren; Rajarajan, Muttukrishnan; Zisman, Andrea (Recent Trends in Network Security and Applications, 2010)
With the proliferation of universal clients over Internet, use of security protocols is rapidly on rise to minimize associated risks. Security protocols are required to be verified thoroughly before being used to secure applications. There are several approaches and tools exist to verify security protocols. Out of these one of the more suitable is the Formal approach. In this paper, we give an overview of different formal methods and tools available for security protocol verification.